Sealing Behavior and Flow Mechanism of Expandable Material Slurry with High Water Content for Sealing Gas Drainage Boreholes - Guozhong Hu; Wenrui He; Changjin Lan (Geofluids)
Predrainage of coalbed gas by underground drilling is one of the main approaches for eliminating gas disasters in coal mines. Owing to the unsatisfactory sealing effect of conventional sealing materials, coalbed gas drainage boreholes face serious air leakage, resulting in a relatively low concentration of the drained gas. This study presents a new grouting solidification method for sealing boreholes using expandable materials with high water content. An experimental test method was used to study the groutability, compression resistance, and gas permeability of the expandable materials with high water content, as well as their binding properties with coal mass at different water-cement ratios. On this basis, the governing equation for slurry permeation considering the viscosity time-varying characteristics of the expandable material with high water content was established and numerically calculated. The slurry permeation patterns of the expandable material with high water content under different grouting pressures and water-cement ratios were obtained. The results show the following: (1) the expandable material with high water content was better than cement to bind with coal mass; (2) the slurry of expandable material with high water content, with a water-cement ratio above 6 : 1, is groutable, and as the water-cement ratio increases, the groutability and penetrability of the expandable material with high water content increase; (3) the optimal grouting pressure for expandable slurry with high water content is 2-3 MPa; and (4) the higher the water-cement ratio, the greater the permeation range of expandable slurry with high water content, but the increase in the permeation range is relatively small, and the optimal water-cement ratio for expandable slurry with high water content is 7 : 1. Therefore, featuring strong groutability, good sealability, high compressive strength, microexpansion, and tight binding with coal mass, expandable materials with high water content are ideal for sealing coalbed gas drainage boreholes because of their efficiency in sealing fractures in coal and rock masses around the borehole.